Diseño Editorial para la difusión de los servicios de la Empresa Metálicas Pillapa en el sector Carrocero - Dumán Pillapa, Christian Timoteo (2024)
The company "Metálicas Pillapa" is dedicated to the construction of buses for various services, including intracantonal, school, intraprovincial, tourist, intraregional and interprovincial. The company does not have better editorial material where it can publicize its various products and services and is known by word of mouth from customers who are satisfied with its product. This is why this project focuses on improving the dissemination of the company's services through the development of editorial material. In order to inform the different products and services offered by the company. Through interviews and different observation sheets it was possible to collect the necessary information to see how the two variables, the bodywork sector and the editorial design for the diffusion of services, are currently. Thus, the resulting proposal consists of editorial materials such as a catalog that allows to publicize the different models of buses and their manufacturing process. It was also developed infographics that highlight the additional important points of manufacture such as adaptation and the different customizations it has. Through these means of dissemination will be made known to members of the company through a training where they can be aware of how to use and what these editorial materials are for..